1975
DOI: 10.1111/j.1439-0329.1975.tb00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Wachstum, Mykorrhiza und Frostresistenz von Fichtenjungpflanzen bei Düngung mit verschiedenen Stickstoffgaben

Abstract: Growth, mycorrhiza and frost resistance of Picea abies seedlings following fertilization with different levels of nitrogen. NPK fertilization with varying levels of nitrogen causes increased growth of spruce seedlings and faster flushing in spring. During the growing season, the frost resistance of all organs of the plants, especially new needles and shoots is the lower, the more nitrogen the plants have received. Consequently, spruce plantations, especially at high altitudes, may be liable to late frost damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…often reported to have a negative influence on frost This could indicate that frost hardiness in these species hardiness (Huokuna and Hiivola 1974, Christersson is not necessarily inhibited by excess of nitrogen. This 1975, Pumpel et al 1975, Arsvoll and Larsen 1977 is supported by studies on alfalfa which Levitt 1980, Tyler et al 1981, Stimart and Gooman indicated a positive correlation between frost hardiness 1985). Most of the studies on interaction between nitro-and nitrogen fertilization (Vezina and Nadeau 1991).…”
mentioning
confidence: 76%
“…often reported to have a negative influence on frost This could indicate that frost hardiness in these species hardiness (Huokuna and Hiivola 1974, Christersson is not necessarily inhibited by excess of nitrogen. This 1975, Pumpel et al 1975, Arsvoll and Larsen 1977 is supported by studies on alfalfa which Levitt 1980, Tyler et al 1981, Stimart and Gooman indicated a positive correlation between frost hardiness 1985). Most of the studies on interaction between nitro-and nitrogen fertilization (Vezina and Nadeau 1991).…”
mentioning
confidence: 76%
“…On the other hand, a high concentration of N can delay the onset of dormancy and thus increase the risk of damage during early frost episodes in autumn (Cannell and Sheppard 1982;Burke et al 1992). From a N fertilisation experiment with spruce seedlings it was concluded that the more N the seedlings received, the faster they flushed in spring, and the more sensitive the new needles and shoots were to frost during the growing season (Pümpl et al 1975). An increased number of injured cells during winter has also been measured in the needles of Scots pine trees which had been fertilised with excess N (Soikkeli and Kärenlampi 1984).…”
Section: Introductionmentioning
confidence: 97%
“…This practice of fall nutrient loading can contribute to enhanced seedling stress resistance [110]. For example, in spruce species increased nitrogen application in seedlings that have already set bud increases freezing tolerance [111][112][113][114][115], while low nitrogen application limits the development of freezing tolerance [42]. Douglas-fir seedlings with budset and low nitrogen levels were less cold hardy than seedlings with higher nitrogen levels [116].…”
Section: Cultural Practicesmentioning
confidence: 99%
“…In reviewing early literature on potassium use as a cultural practice in cold hardening, Timmis [116] concluded that the balance between potassium and nitrogen determines the level of cold hardiness. In studies with spruce species, phosphorus application promotes freezing tolerance [119], while in other instances there was little effect [112,113,118]. The role of nitrogen, potassium and phosphorous in developing freezing tolerance appears to vary with species, rate and timing of application in the nursery [11,17,[120][121][122]].…”
Section: Cultural Practicesmentioning
confidence: 99%